Susceptibilidade do esmalte dentário fluorótico ao desafio erosivo e abrasivo - Silva, Cristiane Araújo Maia (2022)
Pathological conditions of hard dental tissues can be pre- or post-eruptive in nature, such as enamel fluorosis and erosive tooth wear (ETW), respectively. Fluorosis is caused by chronic and excessive fluoride ingestion during enamel development, leading to increased fluoride concentration and porosity. ETW results from exposure of teeth to acid attacks associated or not with abrasion, leading to loss of tooth structure and morphological changes. This in vitro study tested the hypothesis that fluorotic enamel presents different susceptibilities to dental erosion-abrasion. The experimental design used was a 3×3×2 factorial, considering: a) fluorosis severity: healthy (TF0), moderate (TF1-2), severe (TF3-4); b) abrasive challenge: low, medium, high; and c) erosive challenge: yes, no. A total of 144 human teeth were selected according to the three levels of fluorosis severity (n=48), and subdivided into six groups (n=8) generated by the association of different erosive and abrasive challenges. Enamel blocks (4×4mm) were prepared from each tooth and their natural enamel surfaces (unprepared) subjected to an erosion-abrasion cycling model using 1% citric acid with pH around 2.4. After cycling, the depth of wear of the enamel lesions was evaluated for comparison with the initial measurements made by profilometry. Acid exposure caused significantly more enamel surface loss than water (p<0.001). ANOVA showed that the triple and double interactions between the factors were not significant (p>0.20). Enamel fluorosis level (p=0.638) and abrasion level (p=0.390) had no significant effect on lesion depth. In this in vitro study, fluorosis, regardless of the level of severity, did not affect enamel susceptibility to tooth erosion-abrasion.